The Neonatal Innate Immune Response to Sepsis: Checkpoint Proteins as Novel Mediators of This Response and as Possible Therapeutic/Diagnostic Levers - Hensler, Emily; Petros, Habesha; Gray, Chyna C.; Chung, Chun-Shiang; Ayala, Alfred; Fallon, Eleanor A. (Frontiers in Immunology, 2022)
Sepsis, a dysfunctional immune response to infection leading to life-threatening organ injury, represents a significant global health issue. Neonatal sepsis is disproportionately prevalent and has a cost burden of 2-3 times that of adult patients. Despite this, no widely accepted definition for neonatal sepsis or recommendations for management exist and those created for pediatric patients are significantly limited in their applicability to this unique population. This is in part due to neonates’ reliance on an innate immune response (which is developmentally more prominent in the neonate than the immature adaptive immune response) carried out by dysfunctional immune cells, including neutrophils, antigen-presenting cells such as macrophage/monocytes, dendritic cells, etc., natural killer cells, and innate lymphoid regulatory cell sub-sets like iNKT cells, γδ T-cells, etc. Immune checkpoint inhibitors are a family of proteins with primarily suppressive/inhibitory effects on immune and tumor cells and allow for the maintenance of self-tolerance. During sepsis, these proteins are often upregulated and are thought to contribute to the long-term immunosuppression seen in adult patients. Several drugs targeting checkpoint inhibitors, including PD-1 and PD-L1, have been developed and approved for the treatment of various cancers, but no such therapeutics have been approved for the management of sepsis. In this review, we will comparatively discuss the role of several checkpoint inhibitor proteins, including PD-1, PD-L1, VISTA, and HVEM, in the immune response to sepsis in both adults and neonates, as well as posit how they may uniquely propagate their actions through the neonates innate immune response. We will also consider the possibility of leveraging these proteins in the clinical setting as potential therapeutics/diagnostics that might aid in mitigating neonatal septic morbidity/mortality.